Exercise as treatment for alcohol use disorder: A qualitative study. (8th September 2022) - Gunillasdotter, Victoria; Andréasson, Sven; Hallgren, Mats; Jirwe, Maria
Abstract: Introduction: Exercise is a promising treatment option for individuals with alcohol use disorder, but qualitative studies are lacking. Our aim was to explore experiences of yoga and aerobic exercise among non‐treatment‐seeking adults with alcohol use disorder. Methods: Semi‐structured qualitative interviews (face‐to‐face or telephone) with 12 participants from a randomised controlled trial. Qualitative content analysis was used to analyse data. Results: One main category was identified, motivating and maintaining a lifestyle change, including four generic categories: (i) Initiating factors for lifestyle change, which describes how the concept of a lifestyle change initiated participants change; (ii) Influencing lifestyle change, explains how mood‐enhancing effects from exercise influence exercise behaviours; (iii) Influencing physical and mental health, which describes how improvements in physical and mental health influence self‐confidence and self‐esteem; and (iv) Influencing alcohol consumption, which describes how exercise reduced alcohol cravings and that success in changing exercise behaviours made participants take healthier decisions regarding their alcohol intake. Discussion and Conclusions: Exercise may help reduce alcohol intake, especially when presented in the context of a lifestyle change. Being able to self‐select the type of exercise may increase compliance and optimise these benefits. Intentional planning and positive results from exercise may strengthen the individual's self‐efficacy and increase the motivation to change behaviours associated with alcohol consumption.